Remediation institute under the environmental legislation of the Republic of Kazakhstan - Marat, Н.М.; Sopykhanova, А.Б.; Bekturganova, А.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article provides a comprehensive scientific and legal analysis of the remediation institute in the legislation of the Republic of Kazakhstan in the context of the development of the “green economy” and the modernization of environmental regulation. The relevance of the study is determined by the insufficient theoretical development of this institute, the fragmented nature of the regulatory framework, and the absence of a unified law enforcement practice, which is particularly significant in the context of industrial development and active subsoil use. The purpose of the study is to identify the legal nature of remediation, analyze its content, and determine directions for improvement in accordance with the principles of sustainable development. The research employs formal-legal, system-structural, comparative-legal, and logical-doctrinal methods. It has been established that the modern model of legal regulation of remediation in Kazakhstan has evolved from a compensatory approach, based on monetary compensation for environmental damage, to a restorative model focused on achieving actual environmental outcomes. The Environmental Code defines remediation as a set of mandatory measures aimed at restoring environmental components to their baseline condition, implemented through a remediation program with elements of control, monitoring, and transparency. The scientific novelty of the work lies in substantiating remediation as an independent cross-sectoral legal institute that goes beyond environmental regulation. The current legislation of the Republic of Kazakhstan establishes the remediation institute within the framework of environmental law. Problems of coordination between environmental, land, and subsoil use legislation, differences in terminology, and insufficient clarity regarding the legal status of participants in remediation relations have been identified. The necessity of forming remediation as an independent cross-sectoral legal institute is justified. Proposals for improving legislation include unifying the conceptual framework, developing procedural mechanisms for implementing remediation, and strengthening the scientific doctrine in this field. The study concludes on the need to transition to an integrated model of restorative environmental regulation aimed at ensuring environmental safety and sustainable development.